An improved model to evaluate the performance of solar-aided power generation plants. Issue 3 (19th February 2022) - Zhang, Hongsheng; Hu, Eric; Duan, Chenghong; Qin, Jiyun
ABSTRACT: Solar aided power generation (SAPG) is an efficient method to utilize solar thermal energy to generate power in association with traditional fossil-fueled power plants. In an SAPG plant, solar energy is used to replace extracted steam to preheat feedwater into the boiler in a regenerative Rankine power cycle. In previous SAPG plants' performance evaluation models, a key assumption made is that the parameters at the outlets of the boiler, such as temperature and pressure, remain unchanged even if the steam mass flow rates through the boiler have changed due to the introduction of solar heat. This assumption actually makes the boiler to be modeled as a black box to simplify the model, but inevitably compromised the accuracy of the evaluation results. The error is sometimes so significant that some research conclusions are affected especially when the solar heat is used to replace the extraction steam before the reheating process. An improved SAPG evaluation model with the assumption that the boiler is modeled as a heat exchanger instead of a black box is proposed in this paper. The improved model accuracy has been demonstrated focusing on three SAPG power plants, namely 210 MW, 300 MW and 600 MW power plant. The errors are respectively reduced by 0.48%, 2.86% and 0.76% at 50% load. Moreover, three cases studies have been discussed focusing on the three SAPG power plants. The solar-power efficiency of replacing the second extraction steam is lower than that of replacing the third extraction steam after the error of boiler "black box" model is considered. The results indicate that using solar energy to replace higher stage of extraction steam is not necessarily better than replacing lower stage extraction steam as previously understood. The research provides a new insight into the role of solar replacement for different extracted steam levels in an SAPG power plant.